Self-interest over ethics: firm withdrawal from Russia after the Ukraine invasion - Patel, Pankaj (Journal of business ethics, 2025)
Drawing on contrasting theoretical perspectives of self-interest and utilitarian/ethical motivations, we examine the degree to which a company's pace of departure from Russia after the Ukraine invasion is driven by its exposure to the Russian market. Moreover, we investigate whether firm-level political and non-political risks influence the propensity to delay or expedite the exit/withdrawal process. Contrary to utilitarian expectations advocating for ethical exit decisions irrespective of exposure and risks, firms with higher Russian exposure were less likely to exit sooner, indicating a prioritization of business interests over ethical imperatives. This self-interest effect was further amplified by heightened political risks but attenuated by non-political risks. These findings remained consistent across various model specifications, with limited discernible variations based on firm characteristics such as ranking, COVID-19 exposure and risk, past idiosyncratic volatility, or family ownership and control. In addition, an examination of post-exit effects on profitability, risk, cost of capital, and liquidity revealed no statistically significant relationships. Our study highlights the prevalence of self-interest motivations over utilitarian principles, as firms with substantial Russian exposure prioritized safeguarding their business interests in the aftermath of the Ukraine invasion, even at the potential cost of ethical and social responsibility imperatives.